Chitinase-primed ultrasound enhances Saccharomyces cerevisiae cell-wall deconstruction and yeast-protein remodelling in two complementary model systems - Talha Riaz; Xianjiang Ye; Te Yu; Zhijun Xia; Muhammad Moeid Khan; Xuan Yao; Rabiya Riaz; Sadia Ansar; Zhou Chen; Muhammad Atiq Ashraf; Chuanyan Pan; Yongguo Jin; et al. (Food Research International, 2026)

Integrated molecular sensory profiling reveals the distinct aroma signatures of peach fruit types - Wei Zhu; Xiaolin Chen; Zhimeng Gan; Kaijie Zhu; Huaping He; Muhammad Atiq Ashraf; Furong Wang; Yuan Liu; Xizhou Hu; Yang Zhang; Juan Xu; Xiaoyan Ai (Food Research International, 2026)

Clove oil in combination with flurbiprofen attenuated imiquimod-induced psoriasis-like skin inflammation in a mouse model: A mechanistic study - Qianqian Xing; Shuaijie Wang; Hafiz Muhammad Zubair; Aqib Mustafa; Atiq-Ur-Rehman; Hafiza Sidra Yaseen; Farzana Andleeb; Muhammad Asif; Ning Guan (Inflammopharmacology, 2026)

Jasmonic Acid and Abiotic Stress Tolerance: From Metabolic Flux to Hormone-Network Decision Making - Nazma Khan; Burhan Khalid; Muhammad Atiq Ashraf; Umair Khan; Rizwan Maqbool (Journal of Plant Growth Regulation, 2026)

Food security dynamics in South Asia: a multi-method analysis using Random Forest and Error Trend Seasonal models - Muhammad Atiq-ur-Rehman; Sadia Mustafa; Ayesha Hussain; Irfan Hussain Khan; Fatima Akhtar; Sadaf Javed; Azma Batool (Environment, Development and Sustainability, 2026)

Flash flood susceptibility assessment using an integrated geomorphologic framework in data-scarce arid and semi-arid regions - Aftab Ullah; Rashid Farooq; Abdul Razzaq Ghumman; Muhammad Ejaz Tanveer; Muhammad Atiq Ur Rehman Tariq (Modeling Earth Systems and Environment, 2026)
Flash floods are among the most frequent natural hazards, posing serious environmental challenges, particularly in arid and semi-arid regions where steep topography and compact basin morphometry accelerate surface runoff. The ungauged hill torrents of southwestern Punjab, Pakistan, are particularly vulnerable to such events, experiencing recurrent, intense flash floods. This study develops an integrated GIS-based morphometric framework to assess flash flood susceptibility across 13 major hill torrents in DG Khan and Rajanpur, Punjab. Fifteen morphometric parameters were analyzed using three complementary approaches: Hazard Degree (HD), Principal Component Analysis (PCA), and Analytical Hierarchy Process (AHP). The HD method captured the cumulative influence of all parameters. At the same time, PCA reduced redundancy and identified four dominant controlling factors: length of overland flow (Lo), form factor (Ff), circulatory ratio (Rc), and ruggedness number (Rn). The AHP further incorporated expert judgment, identifying drainage density (Dd) and ruggedness number as the most influential parameters, followed by basin relief (Bh) and drainage frequency (Fs). The convergence of results across the three independent methods significantly improves classification reliability compared to single-method analyses. Three hill torrents (Vidore, Mithawan, and Kaha) were consistently classified as highly susceptible, one as moderately susceptible, and four as low susceptibility. Hence, the proposed integrated HD-PCA-AHP model reduces methodological uncertainty and provides a transferable, data-efficient tool for assessing flash flood susceptibility and managing watersheds in data-scarce arid and semi-arid regions.

RETRACTED ARTICLE: Modification of a nonlinear transfer-function noise model for the estimation of groundwater recharge - Saad Zaheer; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem (Hydrogeology Journal, 2026)

Processing sequence as a design lever: pectin pre-complexation enhances ultrasound-driven interfacial loading, functionality, and volatile profile of yeast protein - Talha Riaz; Yuan Ma; Zhijun Xia; Muhammad Moeid Khan; Xianjiang Ye; Muhammad Atiq Ashraf; Rabiya Riaz; Xing Fu; Yongguo Jin (Food Research International, 2026)

A comparative analysis of crop water footprint, practices, and economic water productivity (EWP) in Punjab, Pakistan and Western Australia, Australia - Zohreh Rajabi; Stephen Gray; Shakeel Hayat; Muhammad Atiq Ur Rehman Tariq (Irrigation Science, 2026)
A comprehensive analysis of crop water footprint (WFP), water use efficiency (WUE) and economic water productivity (EWP) between 2010 and 2020 in two climatically and economically diverse agricultural regions: Punjab, Pakistan and Western Australia, Australia was undertaken. Using the Water Footprint Network method and climate, soil and agricultural production data, the study quantified green, blue and grey water footprints for five staple crops in each region. Normalization by local water scarcity and irrigation share was used to compare between the two regions with different water stress levels and irrigation dependence. Results showed that the total crop water requirements in Punjab increased by 12% during the study period due to changing climatic conditions. Cotton and rice had the highest WFP and dependence on irrigation, however generated relatively low economic returns per unit of water, showcasing inefficiency in the current agricultural system. In contrast, rain-fed crops in WA showed lower absolute crop water requirements and lower increases in normalized WFP, with stable WUE and EWP with cereals, showcasing efficient water use under climate-driven limitations. Normalization highlighted the difference in water stress, identifying that Punjab’s irrigation-intensive crops put much greater stress on local water resources than WA crops. Integration of biophysical and economic indicators, when normalizing for water scarcity, provides a strong basis to assess water practice of various agricultural systems. The results indicate the necessity for location-specific approaches: increased irrigation efficiency and suitable crop selection in Punjab; and climate-resilient cropping to maximize water use productivity and economic return in WA.

Integrating CMIP6 climate projections with community-based vulnerability assessment for climate resilience in Haripur, Pakistan - Syed Shujaat Ali; Sabahat Isha; Hamza Paracha; Abdullah Nadeem; Muhammad Atiq Ur Rehman Tariq (Theoretical and Applied Climatology, 2026)

Correction: Modulation of inflammatory and oxidative stress pathways by ethanolic extract of Suaeda fruticosa Forssk. Ex J.F.Gmel in animal models of ulcerative colitis - Juan Liu; Aqib Mustafa; Muhammad Fiaz; Hafiz Muhammad Zubair; Tahir Maqbool; Atiq ur Rehman; Muhammad Asif; Jing Yang (Inflammopharmacology, 2026)

Atraric acid mitigates the cognitive and pathological deficits in mice via Aβ1−42 induced Alzheimer’s disease - Waqar Ali; Kyonghwan Choe; Talha Nasir; Uzair Atiq; Muhammad Tahir; Waqas Ahmad; Hyun Young Park; Tae Ju Park; Myeong Ok Kim (Inflammopharmacology, 2026)

Modulation of inflammatory and oxidative stress pathways by ethanolic extract of Suaeda fruticosa Forssk. Ex J.F.Gmel in animal models of ulcerative colitis - Juan Liu; Aqib Mustafa; Muhammad Fiaz; Hafiz Muhammad Zubair; Tahir Maqbool; Atiq ur Rehman; Muhammad Asif; Jing Yang (Inflammopharmacology, 2026)

Bacterial biological control agents and resistance resources to enhance defense and morphological attributes of Capsicum annuum against Fusarium wilt - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Muhammad Sagheer; Ye Xia (Journal of Plant Pathology, 2026)
Fusarium wilt (c.o. Fusarium oxysporum f. sp. capsici ( Foc ) is one of the major disasters during chilli production, which causes tremendous yield losses under suitable climatic conditions worldwide. One of our research aims was to investigate the incidence of Fusarium wilt disease, with a special reference to the climatic conditions in various chilli growing areas of Punjab, Pakistan, in 2020–2022. For these purposes, three major chilli growing areas were surveyed. All the investigated climatic factors, such as air and soil temperature, relative humidity, rainfall, wind speed, and soil moisture, positively correlated with disease development. The highest disease incidence was recorded in District Lahore (69%), followed by a disease incidence of 31.8% in Chiniot and 16% in Kasur. In our study, two years’ screening (2020-21 and 2021-22) of thirty different chilli varieties/advanced lines was carried out to find out the source of resistance against Fusarium wilt. Among them, only two varieties (Sayban and HP-1810 F1) showed resistance responses, but six varieties (Maxi, PR-0921, BS Hari Rani, FS-1, Janbaz-F1, and Sitara 80) were highly susceptible to Fusarium wilt of chilli. For the disease management with biocontrol agents (BCAs), Bacillus subtilis (MU_Bs09) was found the most effective in inhibiting pathogen mycelial growth (82.68%) and reducing disease incidence (75.88%) under both lab and greenhouse experiments, followed by Streptomyces palmae (MU_Sp19) and Pseudomonas simiae (MU_Ps13). Also, treatment with Bacillus subtilis (MU_Bs09) significantly enhanced the production of some biochemical enzymes and compounds, including catalases, phenolics, H₂O₂, and chlorophyll. In addition, Bacillus subtilis (MU_Bs09) improved the plant morphological attributes, such as fresh weight, dry weight, plant height, and yield per plant when treated at three different concentrations. The related enhancements were followed by Streptomyces palmae (MU_Sp19) and Pseudomonas simiae (MU_Ps13). In conclusion, cultivating resistant plant varieties is one of the most effective strategies to combat Fusarium wilt. In addition, applying soil drenching with beneficial microbes, such as Bacillus subtilis strain MU_Bs09, can be one effective strategy for managing Fusarium wilt through enhancing plant antioxidant activity and other constitutive defense mechanisms.

Characterization and fungicidal sensitivity of Phytophthora species causing citrus gummosis in Pakistan - Hadeed Ahmad; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Muhammad Hamza Shahid; Muhammad Usman Ali; Owais Iqbal; Muhammad Luqman Aleem; Qurban Ali; Nasir Ahmed Rajput (Physiological and Molecular Plant Pathology, 2026)

Precision Rewiring of Stress-Responsive Gene Networks Via CRISPR: Mechanistic Pathways Toward Climate-Smart Agriculture - Burhan Khalid; Muhammad Umer Javed; Muhammad Ikram; Muhammad Ateeq; Muhammad Atiq Ashraf; Talha Riaz; Shumaila Nawaz; Rizwan Maqbool (Journal of Crop Health, 2026)

Photoperiod and temperature: Key abiotic drivers of horticultural crop physiology in a changing climate - Muhammad Atiq Ashraf; Shumaila Nawaz; Uzma Bilal; Maria Abubakar; Shumaila Anam; Muhammad Azam; Burhan Khalid; Abdullah; Muhammad Asim; Rabbya Rayan Shah; Muhammad Ateeq (Biologia, 2026)

Evaluation of Polystyrene Biodegradation: Characterization of biodegradation kinetics of Rhizopus oryzae Strain NA1 at Mesophilic Temperature - Sadia Mehmood Satti; Naima Atiq; Asim Abbasi; Safia Ahmed; Muhammad Adnan Shereen; Aftab Ahmad; Abeer Hashem; Najla A. Alshaikh; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (Water, Air, & Soil Pollution, 2025)

Optimizing tree crown density of finite coastal vegetation patches for enhanced tsunami mitigation - Fakhar Muhammad Abbas; Ali Abdullah Zaid Aldrees; Sohail Iqbal; Amina; Muhammad Atiq Ur Rehman Tariq; Naveed Anjum; Mujahid Iqbal; Usman Ghani; Ghufran Ahmed Pasha (Natural Hazards, 2025)

Understanding flood behavior in the Kashmir Himalayas through copula-driven models - Ishfaq Gujree; Shafique ur Rehman; Joshal K. Bansal; Ningsheng Chen; Aijaz Ahmad Reshi; M. Sultan Bhat; Muhammad Atiq Ur Rehman Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Propolis enhanced sodium alginate hydrogel enriched with copper doped mesoporous bioactive glass nanoparticles for advanced burn care applications - Aqsa Aizaz; Muhammad Haseeb Nawaz; Muhammad Sameet Ismat; Md Abdur Rashid; Muhammad Atiq Ur Rehman (Biotechnology Letters, 2025)

Impact Analysis of Climate Change, Socioeconomic Development, and Hydropower Generation on Water Availability in the Chitral River Basin Using Water Evaluation and Planning (WEAP) Model - Bushra Zaman; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem; Muhammad Kaleem Sarwar; Muhammad Waseem; Mudassar Iqbal; Shakeel Hayat; Khalil Ahmed; Muhammad Usman (Water Conservation Science and Engineering, 2025)
Water, energy, and food are three major issues of concern because of the rapid growth of the population and economy, which are exacerbated by climate change. The disparity between the availability and demand of water is largely driven by domestic and agricultural uses, and it is important to evaluate its impact on hydropower generation. This study aims to integrate climate change, socioeconomic development, and hydropower generation analysis using the water evaluation and planning model (WEAP). This study uses the CMIP6 model to make future projections under shared socioeconomic pathways (SSPs). This study examined the projections of water demand under different scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) using the MPI-ESM1-2HR climate change model. In the reference year 2000, domestic water demand stood at 15 MCM, escalating to 54 MCM under the SSP5-8.5 scenario. Concurrently, agricultural water demand, which was 93.72 MCM in 2000, is projected to surge to 197.35 MCM by 2050. Based on expected future changes in streamflow, the results show that Golen Gol’s hydropower potential varies with the effects of socioeconomic and climatic changes. However, the fluctuation in hydropower generation is more prominent during June and July, leading to an increase in hydropower in future scenarios. The study findings suggest that by 2050, the combination of population growth and agricultural expansion will substantially escalate water demand, posing risks to both the environment and human populations. Consequently, adopting enhanced irrigation methods, refining agricultural techniques, and erecting water conservation and retention infrastructures could effectively mitigate these challenges. To formulate sustainable water management strategies, it is advised to further utilize the integrated water–energy–food nexus approach, strengthened by merging WEAP with the energy modeling program Low Emissions Analysis Platform (LEAP) for hydropower generation.

Correction: Mathematical Modelling for Predicting Wastewater Treatment Efficiency Through Specialised Electrocoagulation - Monzur Alam Imteaz; Muhammad Atiq Ur Rehman Tariq; Zohreh Rajabi; Amimul Ahsan (International Journal of Environmental Research, 2025)

Mathematical Modelling for Predicting Wastewater Treatment Efficiency Through Specialised Electrocoagulation - Monzur Alam Imteaz; Muhammad Atiq Ur Rehman Tariq; Zohreh Rajabi; Amimul Ahsan (International Journal of Environmental Research, 2025)
Based on experimental results on different pollutants removal efficiencies through a specialized electrocoagulation system, simple mathematical models were developed for the predictions of pollutants’ removal efficiencies for any combination of input conditions. Based on earlier experimental results two independent variables, flowrate and voltage were considered for the derivations of the generalized equations. Based on individual experimental results, relationships between flowrate and pollutant removal efficiency was derived using best-fit relationship for eight different pollutants; BOD, COD, Ammonia, TSS, TDS, Chloride, Turbidity and Hardness. Then individual relationships for different voltages were amalgamated to a single equation, which is capable to predict the specific pollutant removal efficiency for any flowrate under any voltage. Except Ammonia and TSS, developed models’ predicted results are having excellent match with the measured pollutants’ removal efficiencies having correlation coefficients (R 2 ) between modeled and measured values ranging from 0.99 to 1.0. Correlation coefficient values for Ammonia and TSS were 0.96 and 0.94 respectively. Other standard error statistics were also low; RMSE ranging from 0.21 to 3.54, MAE ranging from 0.17 to 2.33 and RAE ranging from 0.0 to 0.08. Among all the developed models, highest performing model was for the BOD having an R 2 value of 1.0 and RAE value of 0.0.

First report of Curvularia hawaiiensis causing leaf spot disease of grape in Pakistan - Muhammad Usman Ali; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Owais Iqbal; Muhammad Hamza Furqan; Ahmad Nawaz; Hamza Tariq; Ghalib Ayaz Kachelo; Nasir Ahmed Rajput (Journal of Plant Pathology, 2025)

Unveiling the future: Breakthroughs and innovations in MXene-based electrochemical sensors - Muhammad Khan; Xiaohui Sun; Faisal Attique; Muhammad Tahir Saleh; Naveed Ahmad; Kainat Atiq; Muhammad Shafi; Inas A. Ahmed; Imad Barsoum; Muhammad Shahbaz Rafique; Azeem Ullah; Amjad Hussain; et al. (Chemical Engineering Journal, 2025)

Dust trace metals implications on school’s indoor air quality linked to human health risk at Khurianwala (Pakistan) - Muhammad Hassan Bashir; Atiq ur Rehman; Hamaad Raza Ahmad; Amor Hedfi; Manel Ben Ali; Fehmi Boufahja; Khaled Elmnasri; Ezzeddine Mahmoudi; Muhammad Tahir Shehzad (Atmospheric Environment, 2024)

Improving Irrigation Performance of Raised Bed Furrow Using WinSRFR Model - Muhammad Ayub Shah; Muhammad Waseem; Mudassar Iqbal; Ghulam Nabi; Muhammad Atiq Ur Rehman Tariq; Abu Bakar Arshed; Umar Sultan; Muhammad Laraib; Khawar Abbas (Water Conservation Science and Engineering, 2024)
Agricultural productivity is intricately tied to efficient water management strategies, with raised bed furrow systems being a prevalent method for irrigation. However, the optimization of these systems remains a critical area of exploration. The border irrigation method is commonly employed in developing countries for irrigation and leads to significant water loss, reduced irrigation efficiency, and increased irrigation durations. In contrast, raised bed furrow irrigation represents an improved surface irrigation technique that optimizes water usage in irrigated systems. This study seeks to assess the irrigation performance of raised bed furrows, encompassing deep percolation loss, distribution uniformity, adequacy, and application efficiency. The evaluation will be conducted for both existing conditions and an optimized scenario achieved through the application of the WinSRFR model. Field data facilitated the numerical simulation and the model was calibrated to reflect the existing irrigation system dynamics accurately. The performance of the model was assessed by utilizing the statistical indicator of root mean square error (RMSE) and revealed good agreement between advance and recession time. Results revealed that existing raised bed furrow irrigation exhibited up to 40% deep percolation loss, 80% distribution uniformity, and 60% application efficiency. Increasing furrow length had adverse effects; decreased application efficiency and distribution uniformity; and increased deep percolation losses. In contrast, reducing the furrow length and cutoff time by up to 33% and 40%, respectively, and increasing the width and inflow rate by up to 55% and 100%, respectively, enhanced the application efficiency and distribution uniformity, and minimized deep percolation loss. Overall, improved raised bed furrow irrigation provides a more efficient option and is encouraged to adopt for irrigation.

Microfluidic devices for the isolation and label-free identification of circulating tumor cells - Muhammad Anwar; Nuno M. Reis; Chi Zhang; Adil Khan; Kashif Ali Kalhoro; Atiq Ur Rehman; Yanke Zhang; Zhengchun Liu (Chemical Engineering Journal, 2024)

An integrated land change modeler and distributed hydrological model approach for quantifying future urban runoff dynamics - Asad Hussain Muhammad; Waseem Muhammad; Ajmal Muhammad; Atiq Ur Rehman Tariq Muhammad; Jiaqing Xiao; Tao Yang; Pengfei Shi (Science China Earth Sciences, 2024)

First report of Pythium aphanidermatum causing stem and root rot disease on sesame (Sesamum indicum L.) in Punjab, Pakistan - Nasir Ahmed Rajput; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Owais Iqbal; Muhammad Usman Ali; Muhammad Wahab; Hadeed Ahmad (Journal of Plant Pathology, 2024)

Assessment of future drought sensitivity shift associated with crop yield loss risk in the Anthropocene - Muhammad Waseem; Tahira Khurshid; Muhammad Shahid; Muhammad Atiq Ur Rehman Tariq; Jiaqing Xiao; Tao Yang; Pengfei Shi (Hydrological Sciences Journal, 2024)

Hydrochemical, hydrogeological, and cancer health risk analysis of groundwater due to anthropogenic activities, Hasilpur, Pakistan - Muhammad Irfan Jalees; Muhammad Atiq; Muhammad Umar Farooq; Ghulam Hussain; Mehwish Anis; Qurat Ul Ain; Maira Kaleem; Ahmad Ibrahim (Environmental Monitoring and Assessment, 2024)

Efficacy of Green Synthesized Silver Based Nanomaterials Against Early Blight of Tomato Caused by Alternaria solani - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Shahbaz Talib Sahi; Mohsin Shad; Nian Lili; Shahid Iqbal; Asif Mahmood Arif; Usama Ahmad; Khurram Shehzad Khan; Muhammad Asif; Fasih Ullah Haider (Journal of Crop Health, 2024)

Retraction Note: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Hydrological response under CMIP6 climate projection in Astore River Basin, Pakistan - Zeshan Ali; Mudassar Iqbal; Ihsan Ullah Khan; Muhammad Umer Masood; Muhammad Umer; Muhammad Usama Khan Lodhi; Muhammad Atiq Ur Rehman Tariq (Journal of Mountain Science, 2023)
Climate change strongly influences the available water resources in a watershed due to direct linkage of atmospheric driving forces and changes in watershed hydrological processes. Understanding how these climatic changes affect watershed hydrology is essential for human society and environmental processes. Coupled Model Intercomparison Project phase 6 (CMIP6) dataset of three GCM’s (BCC-CSM2-MR, INM-CM5-0, and MPI-ESM1-2-HR) with resolution of 100 km has been analyzed to examine the projected changes in temperature and precipitation over the Astore catchment during 2020–2070. Bias correction method was used to reduce errors. In this study, statistical significance of trends was performed by using the Man- Kendall test. Sen’s estimator determined the magnitude of the trend on both seasonal and annual scales at Rama Rattu and Astore stations. MPI-ESM1-2-HR showed better results with coefficient of determination (COD) ranging from 0.70–0.74 for precipitation and 0.90–0.92 for maximum and minimum temperature at Astore, Rama, and Rattu followed by INM-CM5-0 and BCC-CSM2-MR. University of British Columbia Watershed model was used to attain the future hydrological series and to analyze the hydrological response of Astore River Basin to climate change. Results revealed that by the end of the 2070s, average annual precipitation is projected to increase up to 26.55% under the SSP1–2.6, 6.91% under SSP2–4.5, and decrease up to 21.62% under the SSP5–8.5. Precipitation also showed considerable variability during summer and winter. The projected temperature showed an increasing trend that may cause melting of glaciers. The projected increase in temperature ranges from - 0.66°C to 0.50°C, 0.9°C to 1.5°C and 1.18°C to 2°C under the scenarios of SSP1–2.6, SSP2–4.5 and SSP5–8.5, respectively. Simulated streamflows presented a slight increase by all scenarios. Maximum streamflow was generated under SSP5–8.5 followed by SSP2–4.5 and SSP1–2.6. The snowmelt and groundwater contributions to streamflow have decreased whereas rainfall and glacier melt components have increased on the other hand. The projected streamflows (2020–2070) compared to the control period (1990–2014) showed a reduction of 3%–11%, 2%–9%, and 1%–7% by SSP1–2.6, SSP2–4.5, and SSP5–8.5, respectively. The results revealed detailed insights into the performance of three GCMs, which can serve as a blueprint for regional policymaking and be expanded upon to establish adaption measures.

Urban Heat Island vulnerability mapping using advanced GIS data and tools - Paras Sidiqui; Phillip B Roös; Murray Herron; David S Jones; Emma Duncan; Ali Jalali; Zaheer Allam; Bryan J Roberts; Alexander Schmidt; Muhammad Atiq Ur Rehman Tariq; Ashfaq Ahmed Shah; Nasir Abbas Khan; et al. (Journal of Earth System Science, 2022)

Asymptomatic populus alba: a tree serving as a reservoir of begomoviruses and associated satellites - Roma Mustafa; Muhammad Hamza; Atiq Ur Rehman; Hira Kamal; Muhammad Nouman Tahir; Shahid Mansoor; Brian E. Scheffler; Rob W. Briddon; Imran Amin (Australasian Plant Pathology, 2022)

How do farmers cope with climate change? An analysis of alternative adaptation strategies in drought-hit areas of Khyber Pakhtunkhwa—Pakistan - Imtiaz Alam Khan; Muhammad Rafiq; Sanaullah Panezai; Shahab E. Saqib; Raza Ullah; Muhammad Atiq (Natural Hazards, 2022)

Functional identification of G. hirsutum genes for their role in normal plant development and resistance against Verticillium dahliae using virus-induced gene silencing - Roma Mustafa; Muhammad Javed Iqbal; Muhammad Hamza; Atiq Ur Rehman; Ismail Buzdar; Hira Kamal; Shahid Mansoor; Imran Amin (European Journal of Plant Pathology, 2021)

Socioeconomic impacts of domestic biogas plants on rural households to strengthen energy security - Nadeem Iqbal; Muhammad Arshad Sakhani; Abdul Razzaq Khan; Atiq-ur-Rehman; Zahid Ajmal; Muhammad Zubair Khan (Environmental Science and Pollution Research, 2021)

Determination of insecticide resistance in Bemisia tabaci (Hemiptera: Aleyrodidae) populations from Punjab, Pakistan - Muhammad Saleem; Mansoor ul Hasan; Muhammad Sagheer; Muhammad Atiq (International Journal of Tropical Insect Science, 2021)

First report of Curvularia verruculosa causing leaf spot disease of grape (Vitis vinifera) in Afghanistan - Nasir Ahmed Rajput; Hussainullah; Chao Huo; JiFen Cao; Muhammad Atiq; Rana Muhammad Atif; Abdul Mubeen Lodhi; Rehana Naz Syed; Sohaib Sarfraz; Akhtar Hameed; Zhijian Zhao (Journal of Plant Pathology, 2020)

First report of Fusarium equiseti causing stem rot disease of grape (Vitis vinifera L.) in Afghanistan - Nasir Ahmed Rajput; Bakhat Zaman; Chao Huo; JiFen Cao; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Babar Khan; Owais Iqbal; Zhijian Zhao (Journal of Plant Pathology, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

Multiple alphasatellites associated with Papaya leaf curl virus and Croton yellow mosaic betasatellite in Croton bonplandianus: first identification of Ageratum yellow vein Singapore alphasatellite in Pakistan - Roma Mustafa; Muhammad Hamza; Muhammad Nouman Tahir; Hira Kamal; Muhammad Zuhaib Khan; Atiq ur Rehman; Brian E. Scheffler; Rob W. Briddon; Shahid Mansoor; Imran Amin (European Journal of Plant Pathology, 2019)

RETRACTED ARTICLE: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

First report of Geotrichum candidum causing postharvest sour rot of carrot in Punjab, Pakistan - Akhtar Hameed; Muhammad Waqar Alam; Abdul Rehman; Khalid Naveed; Muhammad Atiq; Nasir Ahmed Rajput; Sohaib Sarfraz; Nadia Liaqat; Faizan Ahmad Tahir (Journal of Plant Pathology, 2019)

N-Pyrazoloyl and N-thiopheneacetyl hydrazone of isatin exhibited potent anti-inflammatory and anti-nociceptive properties through suppression of NF-κB, MAPK and oxidative stress signaling in animal models of inflammation - Sara Zeeshan; Muhammad Naveed; Adnan Khan; Ayesha Atiq; Maryam Arif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammation Research, 2019)

The increasing carbon dioxide (CO2) due to global climate change strengthens the plants and inhibits pathogenic infection - Muhammad Rizwan Bashir; Muhammad Atiq; Muhammad Mohsan (Environmental Science and Pollution Research, 2018)

Correction to: Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Identification of pedilanthus leaf curl virus and associated betasatellite infecting turnip in Pakistan - Samrah Munir; Muhammad Khurshid; Hira Kanwal; Mujahid Hussain; Muhammad N. Sattar; Irfan Ali; Atiq-ur Rehman; Zafar Iqbal (Journal of Plant Pathology, 2018)

Antifungal exploitation of fungicides against Fusarium oxysporum f. sp. capsici causing Fusarium wilt of chilli pepper in Pakistan - Muhammad Rizwan Bashir; Muhammad Atiq; Muhammad Sajid; Muhammad Mohsan; Waseem Abbas; Muhammad Waqar Alam; Muhammad Bashair (Environmental Science and Pollution Research, 2018)

Levels of Organotin Compounds in Selected Fish Species from the Arabian Gulf - Muhammad Waqar Ashraf; Abdus Salam; Atiq Mian (Bulletin of Environmental Contamination and Toxicology, 2017)

Pathogenic diversity of Xanthomonas oryzae pv. oryzae isolates collected from Punjab Province of Pakistan - Hafiz Muhammad Imran Arshad; Kamran Saleem; Junaid Ahmed Khan; Muhammad Rashid; Muhammad Atiq; Syed Sarwar Alam; Shahbaz Talib Sahi (European Journal of Plant Pathology, 2017)

Risk-based flood zoning employing expected annual damages: the Chenab River case study - Muhammad Atiq Ur Rehman Tariq (Stochastic Environmental Research and Risk Assessment, 2013)